2017
DOI: 10.7554/elife.27470
|View full text |Cite
|
Sign up to set email alerts
|

Structure and in situ organisation of the Pyrococcus furiosus archaellum machinery

Abstract: The archaellum is the macromolecular machinery that Archaea use for propulsion or surface adhesion, enabling them to proliferate and invade new territories. The molecular composition of the archaellum and of the motor that drives it appears to be entirely distinct from that of the functionally equivalent bacterial flagellum and flagellar motor. Yet, the structure of the archaellum machinery is scarcely known. Using combined modes of electron cryo-microscopy (cryoEM), we have solved the structure of the Pyrococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
161
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(173 citation statements)
references
References 73 publications
(152 reference statements)
10
161
2
Order By: Relevance
“…Studies have revealed a high degree of conservation, with similar post-translational modifications also observed in other Neisseria strains (Stimson et al, 1995;Craig et al, 2006). Archaella from Pyrococcus furiosus, possess five N-linked glycosylation sites in each FlaB 0 archaellin (Daum et al, 2017), while the Methanospirillum hungatei filament possesses six O-linked and two N-linked glycans per subunit (Poweleit et al, 2016).…”
Section: The Filaments and Their Protomersmentioning
confidence: 54%
See 4 more Smart Citations
“…Studies have revealed a high degree of conservation, with similar post-translational modifications also observed in other Neisseria strains (Stimson et al, 1995;Craig et al, 2006). Archaella from Pyrococcus furiosus, possess five N-linked glycosylation sites in each FlaB 0 archaellin (Daum et al, 2017), while the Methanospirillum hungatei filament possesses six O-linked and two N-linked glycans per subunit (Poweleit et al, 2016).…”
Section: The Filaments and Their Protomersmentioning
confidence: 54%
“…These extend from the cell up to several micrometres in length and are predominantly found in polar regions (Bardy et al, 2002;Nudleman et al, 2006;Gold et al, 2015;Daum et al, 2017) (Figure 1), presumably ensuring co-ordinated and directional movement. Pilins and archaellins are synthesised typically as membrane-integral preproteins that contain a conserved class III signal sequence.…”
Section: The Filaments and Their Protomersmentioning
confidence: 99%
See 3 more Smart Citations